STUDI KASUS PEMODELAN OPERASI POMPA BANJIR KAWASAN JL. MADUKORO KOTA SEMARANG - bakhtiar, faridian; wahyudi, Slamet Imam (Pondasi, 2024)
Madukoro area in Semarang City is a residential, business, shopping, education, office, and warehousing area in the northern coastal area of Tawangmas Village in West Semarang District. Flooding problems have practically disrupted the activities of the area. The drainage system is the root cause of the problem, coupled with the contour and topography of the land which is almost flat without slopes, so it requires an evaluation of the drainage system by recalculating the hydrological and hydraulic aspects and the need for sufficient flood pump performance to overcome flood problems in the Madukoro area. The evaluation of the drainage system includes planning the modeling of the flood pump area. The calculation of the planned flood discharge uses EPA SWMM version 5.1 modeling for a 5-year period and to calculate the frequency analysis of hydrological data using Aprob_4.1. The modeling of an area of 55 ha with restrictions on the catchment area of the Madukoro area which is limited by the Semarang Indah channel on the South side, and the West to North sides are limited by Jl. Arteri Yos Sudarso, and the East side is limited by Kanal Banjir Barat. The calculation of the planned flood discharge is 12.36 m3/s at the Madukoro long storage. From the results of the planned flood discharge, the Madukoro long storage is designed using 2 pumps with a capacity of 1.5 m3/s by maintaining 1 existing pump installed at the location with a capacity of 1.5 m3/s and utilizing 2 existing pumps with a capacity of 0.6 m3/s. For long storage planning, the dimensions are adjusted to existing conditions, namely a width of 6 m with a designed depth of 1.8 m to 3.00 m, a length of 551 m, and the water level is maintained at a depth of 0.4 m to 1.0 m from the bottom of the channel. Meanwhile, the elevation planning of the embankment still uses the existing elevation. Water gates are made at the intersection of the Semarang Indah channel and the Madukoro channel, and at the warehouse location bordering Kanal Banjir Barat.